1996
DOI: 10.1073/pnas.93.8.3308
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the proteasome pathway interfere with induction of nitric oxide synthase in macrophages by blocking activation of transcription factor NF-kappa B.

Abstract: The objective of this study was to elucidate the role of the proteasome pathway or multicatalytic proteinase complex in the induction of immunologic nitric oxide (NO) synthase (iNOS) in rat alveolar macrophages activated by lipopolysaccharide. Macrophages were incubated in the presence of lipopolysaccharide plus test agent for up to 24 hr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
130
0
3

Year Published

1998
1998
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(144 citation statements)
references
References 36 publications
11
130
0
3
Order By: Relevance
“…According to this model, the expression of iNOS is regulated by a combination of LPS-and IFN-induced transcription factors. One aspect of this model that we have previously examined is the necessary role of NF-B for the induction of iNOS in LPS-treated RAW macrophages (38). In the present study, we sought to confirm the role of endogenous IFN-␤ as an autocrine/paracrine activator of iNOS expression, and to determine the timing of downstream events, including activation of the JAK/STAT and IRF signaling pathways, iNOS transcription and translation, and ultimately NO generation.…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, the expression of iNOS is regulated by a combination of LPS-and IFN-induced transcription factors. One aspect of this model that we have previously examined is the necessary role of NF-B for the induction of iNOS in LPS-treated RAW macrophages (38). In the present study, we sought to confirm the role of endogenous IFN-␤ as an autocrine/paracrine activator of iNOS expression, and to determine the timing of downstream events, including activation of the JAK/STAT and IRF signaling pathways, iNOS transcription and translation, and ultimately NO generation.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfasalazine has been reported to inhibit NF-B activation by interfering with phosphorylation of I B␣ (31), whereas calpain inhibitor I inhibits proteosomal degradation of I B (32). Both agents inhibited HRV-16-induced activation of NF-B, preventing the formation of complexes with the oligonucleotides derived from both the IL-6 and IL-8 gene promoter sequences.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that this cytosolic protease complex selectively degrades intracellular proteins and may contribute to the processing of antigens presented by major histocompatibility complex (MHC) class I molecules [41,60,61]. Furthermore, it has been suggested that it may be involved in the regulation of nitric oxide synthase expression [62]. Our results imply that the expression of powerful biological mediators such as TNF and IL-1␤ is regulated by a specific proteolytic system, the proteasome, representing one of the critical steps of control.…”
Section: Discussionmentioning
confidence: 99%